Baseline monocyte and its classical subtype may predict efficacy of PD-1/PD-L1 inhibitor in cancers - Shao, Yilin (Biosci Rep, 2021)
Background: Programmed death 1 (PD-1)/ programmed death-ligand 1 (PD-L1) inhibitor is one of the most popular immune therapies. Biomarkers for predicting response are highly needed, but no biomarkers are widely used till now. Patients and methods: From February 2018 to April 2019, pan-cancer patients treated with PD-1 or PD-L1 inhibitor as a single agent in our center were included. The benefit group included patients with partial response, complete response and stable disease, while the patients with progressive disease were classified into the nonbenefit group, according to the RECIST 1.1 criteria. Baseline peripheral blood was sampled to determine absolute monocyte count (AMC) and/or classical monocyte frequency (CMF) of peripheral blood mononuclear cells. Then, the association of the above-mentioned two biomarkers with response or progression-free survival (PFS) was evaluated. Results: In total, 107 patients enrolled in the present study. The nonbenefit group had significantly larger number of AMC than benefit group (P<0.001), and patients with higher AMC had decreased PFS time (P=0.001). Of 39 patients tested for CMF, the nonbenefit group had significantly higher CMF than benefit group (P=0.002), and patients with higher CMF had significantly decreased PFS time (P=0.002). The sensitivity of AMC and CMF was 87.9% and 85.7%, respectively, and the specificity was 44.9% and 61.1%, respectively. Multivariate analysis showed high baseline CMF and AMC were both significantly associated with decreased PFS time. Conclusion: Baseline CMF and baseline AMC can be potential pan-cancer biomarkers to predict efficacy of PD-1/PD-L1 inhibitors, especially in the PD-L1 subgroup.